Pemisahan Unsur-unsur pada Monasit Bangka dengan Pengendapan Bertingkat - Novriyanisti, Anggi; Prassanti, Riesna; Widana, Kurnia Setiawan (EKSPLORIUM, 2021)
Monazite is a mineral side product of tin processing, which mainly contains uranium (U), thorium (Th), rare earth elements (REE), and phosphate compounds (PO4). Besides these main elements, monazite also contains other metals such as aluminum (Al), iron (Fe), bismuth (Bi), gallium (Ga), and thallium (Tl). The elements in monazite must be separated to be used. This study aims to determine the effect of pH variations in the separation of components in monazite with multilevel precipitation and determine elements produced from each pH variation. The variation pH starts from pH 0,5 to 10 with a different pH of zero points five. The elements in monazite are separated gradually, beginning from the decomposition process using sodium hydroxide (NaOH), dissolving with hydrochloric acid (HCl), and graded deposition with ammonium hydroxide (NH4OH). The elements were analyzed using the instrument Inductively Coupled Plasma Optical Spectroscopy (ICP-OES) and UV-Visible Spectrophotometer. The effect of pH variations produced precipitated pH 3, pH 6, pH 6.5, and pH 7. The elements produced at each pH variation are uranium, thorium, rare earth elements, aluminum, iron, bismuth, gallium, and thallium. Uranium and thorium were mostly at pH 3 with the recovery of U 72.3% and Th 46.33% and rare earth elements at pH 6.5 with 41.87% recovery. The elements Fe and Bi mostly settle at pH 3 with levels of 37.9 ppm and 100.9 ppm. The elements Al, Ga, and Tl, precipitate most at pH 6.5 with grades of 30.2 ppm, 69.8 ppm, and 8 ppm respectively.